Therapy of Brain Exercise on The Quality of Sleeping in Elderly - Ita Irvana; Galia Wardha Alvita; Icca Narayani Pramudaningsih; Vera Fitriana (South East Asia Nursing Research, 2020)
The aging is a natural process that cannot be avoided with age. Even though it is a natural thing, the process of aging still causes problems both physically, biologically, mentally and socio-economically due to a decline which is called a degenerative process The process of degeneration that occurs in the elderly, causes time. World Health Organization (WHO) confirmed that there were 600 million elderly people in 2012 worldwide. WHO also noted that there are 142 million elderly people in the Southeast Asia region. Meanwhile, according to the Central Statistics Agency (BPS), it was noted that the number of elderly people in Indonesia reached 28 million in 2012 from only 19 million in 2006. The results of the data recapitulation of the Central Java health office recorded 3 million elderly people in Central Java. The method in this study was experimental research and quasi-experimental design type with quasi-experimental design and village control group. Sample determination using the Total Sampling technique with a sample size of 30 respondents. Data analysis was performed using the Wilcoxon test. The results obtained before being given an intervention that has a level of good sleep quality amounted to 43.3% and after given an intervention that has a level of quality of sleep that is good, the minimum is 76.7%. Statistically obtained a p-value of 0,000 (<0.05) can be interpreted that there is a significant influence on brain gymnastics on the quality of sleep in the elderly.